Marine metagenomics, a valuable tool for enzymes and bioactive compounds discovery - Barone, Rosalba; De Santi, Concetta; Palma Esposito, Fortunato; Tedesco, Pietro; Galati, Federica; Visone, Marco; Di Scala, Alessia; De Pascale, Donatella (Frontiers in Marine Science, 2014)
The enormous potential in diversity of the marine life is still not fully exploited due to the difficulty in culturing many of the microorganisms under laboratory conditions. In this mini-review we underlined the importance of using an omics technique, such as metagenomics, to access the uncultured majority of microbial communities. We report examples of several hydrolytic enzymes and natural products isolated by functional sequenced-based and function- screening strategies assisted by new high-throughput DNA sequencing technology and recent bioinformatics tools. This article ends with an overview of the potential future perspectives of the metagenomics in bioprospecting novel biocatalysts and bioactive compounds from marine sources.